2020
DOI: 10.1186/s13019-020-1067-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of clinical and morphologic findings in patients with type B aortic intramural hematoma

Abstract: Background: Aortic intramural hematoma (IMH) is a subset of acute aortic syndrome, and its prognosis may differ between races. This study aimed to study the prognosis of Chinese type B IMH patients and to find out risk factors. Methods: A total of 71 type B IMH patients with or without penetrating atherosclerosis ulcer (PAU) administrated in our center between September 2013 and October 2017 were retrospectively studied. Both clinical and imaging data were collected and analyzed. The primary end point was aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…One of nine articles was excluded because it scored less than 5. Finally, eight observational studies 5,6,7,[10][11][12][13][14] were included in the analysis, which enrolled 870 patients who received TEVAR + OMT (n = 446) and OMT (n = 424) from 2004 to 2020 (Supplementary Table S3).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of nine articles was excluded because it scored less than 5. Finally, eight observational studies 5,6,7,[10][11][12][13][14] were included in the analysis, which enrolled 870 patients who received TEVAR + OMT (n = 446) and OMT (n = 424) from 2004 to 2020 (Supplementary Table S3).…”
Section: Search Resultsmentioning
confidence: 99%
“…Finally, the different baseline levels of patients, such as follow-up time, IMH thickness, and disease phase, may lead to the high heterogeneity of the all-cause death and hematoma regression/resolution. Some studies enrolled patients in the acute phase, 5,[11][12][13] while others included patients in all phases. 6,7,10,14)…”
Section: Limitationsmentioning
confidence: 99%
“… 4 However, since mural thrombi and calcifications are not well visible, MRI still represents a second-choice diagnostic tool. 5 In the absence of univocal guidelines and due to the self-limiting nature of the disease, patients with stable haemodynamics and no complications may benefit from medical therapy only 6,7 ; nevertheless, AIH may also complicate into aortic dissection or rupture, both associated with visceral malperfusion ( e.g. stroke or myocardial infarction).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with stable haemodynamics and no complications should be managed with beta-blockers and nitroprusside, keeping systolic pressure under 120 mm Hg. 6,7 On the contrary, acute ULPs, intimal erosions over 20 mm in width or 10 mm in depth, refractory hypertension, uncontrolled pain, progressive pleural effusion, MAD over 45 mm all represent indications for a surgical/endovascular treatment. 1 TEVAR prevents aortic rupture and visceral malperfusion and decreases significantly aorta-specific mortality at 5 years 7 ; the aim is to occlude the entry tear (favouring thrombosis within the false lumen) and to re-expand the true aortic lumen.…”
Section: Outcome Follow-up and Discussionmentioning
confidence: 99%
“…The pathological process of the aortic wall in AD patients will not be terminated by partial aortic resection, and the residual false lumen will face a lifelong risk of long-term neoplasia and rupture [ 10 ]. Studies have shown that the incidence of long-term postoperative complications in AD patients is still high, such as new hairpin layer [ 11 ], aneurysm formation or rupture [ 12 ], endleakage [ 13 ], stent displacement and stent rupture, which seriously affect the quality of life of patients. Therefore, long-term and even lifelong early prevention after surgery are significant.…”
Section: Introductionmentioning
confidence: 99%